Urine Output Assessment in Acute Kidney Injury: The Cheapest and Most Impactful Biomarker - Goldstein, Stuart L. (Frontiers in Pediatrics, 2020)
Acute kidney injury (AKI) is independently associated with morbidity and mortality in critically ill neonates, children, adolescents and young adults. AKI occurs commonly in this population, and the vast majority of published studies utilize only a serum creatinine based criteria for AKI diagnosis and staging. While urine output criteria have been a part of all AKI systematic and multidimensional AKI definitions for the past 15 years, oliguria based on these definitions is difficult to extract from the electronic health record. This manuscript reviews the published data regarding the impact of oliguria on patient outcomes, and the contribution of oliguria to fluid overload and resultant changes in serum creatinine based epidemiology. The aim of this manuscript is to demonstrate that oliguria is an incredibly valuable biomarker for the management of patients with, or at-risk for, AKI.